AGAMA SEBAGAI ALIENASI DALAM PEMIKIRAN KARL MARX: MEMANDANG AGAMA SEBAGAI PELARIAN DARI KRISIS EKONOMI - Prana Ilahi, Restu; Zannah Tanjung, Fathul; Hasibuan, Isma; Burhanuddin, Muhamad (Universitas Nahdlatul Ulama Surakarta, 2024)
This article discusses Karl Marx’s perspective in interpreting religion, and how it is used as motivation for religion. There are many arguments that assume that Karl Marx was an enemy of religious people. The titles communist and materialist are always attached to him, critics who study Karl Marx’s thoughts often conclude that Karl Marx outright rejected the presence of religion. How ever, it does not provide an explanation of what Karl Marx criticized relegion for. Karl Marx’s thougts on religion were very radical and deep in reach. According to Karl Marx, he procces of human life consist of two interconnected aspect, namely religious factors as something sacred (supernatural) and economic factors as problems in the form of science, philosophy and ideologi. Karl Marx’s thoughts on religion were very radical and deep in. So to interpret it requires a deep understanding of it.